El testimonio anticipado y las pruebas de refuerzo en los delitos Sexuales en las Sentencias emitidas por el Tribunal Penal de Chimborazo durante los años 2017-2019 - Nuñez Laje, Erik Andres (2019)
An anticipated or urgent testimony, and reinforcement test within sexual crimes contribute and reinforce victim´s testimony, based on credibility criteria, and supported by technical, scientific and probable evidences. A judge must take into account three perspectives to assess any case such as: A non- subjective disbelief existence, a description verisimilitude from the victim which must be linked with a corroborated the rest of the body of evidence to strengthen story credibility. Finally, there must be persistence in the incrimination, and a double dimension from the ability to convey the truth so much so that of the degree the narrative deserves objectivity. By taking into account the mentioned background, a research has been developed: EARLY TESTIMONY AND REINFORCEMENT PROOFS IN SEXUAL CRIMES IN ISSUED SENTENCES BY PENAL COURT IN CHIMBORAZO PROVINCE FROM 2017 TO 2019. It aims to describe through a doctrinal, scientific and technical analysis and anticipated testimony and reinforcement test in order to be applied in sentences by Criminal Court in Chimborazo Province. A juridical venue is located in Riobamba city. Research methods were inductive, historical-logical, analytical and descriptive, with a qualitative and non-experimental design approach. The population was constituted by six judges and ten trial lawyers. The population involved did not exceed the number of one hundred. Therefore, a formula is not drawn up and the entire population was considered in order to collect information on the topic. An interview guide and survey were applied; then, the results allowed observing that the judges base their criteria on indicia evidence as the only evidence. In a few cases, they assess the reinforcement test as o whole.